Assessment of the Cost of the Mediterranean Diet in a Low-Income Region: Adherence and Relationship with Available Incomes - Alessia Rubini; Cristina Vilaplana-Prieto; Marta Flor-Alemany; Lorena Yeguas-Rosa; Miriam Hernández-González; Francisco Javier Félix-García; Francisco Javier Félix-Redondo; Daniel Fernández-Bergés (BMC, 2022)
Abstract Background The Mediterranean Diet (MD) is recognized as heart-healthy, but the economic cost associated with this type of diet has scarcely been studied. The objective of the present study is to explore the cost and adherence of a low-income region population to the MD and its relationship with income. Methods A population-based study was carried out on 2,833 subjects between 25 and 79 years of age, 54% women, selected at random from the municipalities of Vegas Altas, La Siberia and La Serena in the province of Badajoz, Extremadura (Spain). Average monthly cost of each product included in the MD was computed and related to adherence to the MD using the Panagiotakos Index and average disposable income. Results The monthly median cost was 203.6€ (IQR: 154.04-265.37). Food-related expenditure was higher for men (p<0.001), age cohort between 45 and 54 years (p<0.013) and those living in urban areas (p<0.001). A positive correlation between food-related expenditure and the MD adherence was found. Monthly median cost represents 15% of average disposable income, ranging between 11% for the group with low MD adherence and 17% for the group with high MD adherence. Conclusions The monthly cost of the MD was positively correlated with the degree of adherence to this dietary pattern. Given that the estimated monthly cost is similar to that of other Spanish regions with a higher income level, the economic effort required to be able to afford the Mediterranean diet is higher. This may represent a barrier to access, which should be analyzed in detail by public decision-makers.